Pembisuan Perempuan dalam Film Habibie dan Ainun - Nuraini, Rahmi (Interaksi: Jurnal Ilmu Komunikasi, 2014)
Writing books and filming Habibie and Ainun an attempt of men to remember and bring back women as objects, which makes the male as the subject. Unconsciousness women as objects of male desire in the film Ainun Habibie and this can be understood by analyzing feminist psychoanalysis (biological and psychological differences) with Muted Group Theory approach to the elements which appear in the book and movie. To demonstrate the silencing efforts of men over women, the film was analyzed by the method of semiotics Barthes, through 5 code meaning, denotative and connotative meanings. Signs that were examined in this regard include visual elements (space, color, shape, texture) and non-visual (sound, writing, and verbal).